THE IMPACT OF MONETARY POLICY OVER THE INTEREST RATE: AN EMPIRICAL STUDY - TNR. KAVITHA & S.JAMUNA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
Impact of monetary policy on the interest rate is a study done to find out the relation between the monetary policy changes on interest rate with two Indian public and private sector banks the study helps to find out the relationship between the interest and monetary policy the multiple indicator approach is focusing on the change in the single parameter changes the entire indicators the influence might be direct otherwise indirect. The study aims to find out the relevance of monetary policy review on the quarterly basis and how should be the monetary policy impact the general economy of the country. The cash flow among the public can be controlled by the central bank with a change in the any of the parameter that is the controlling authority of the reserve bank of India. The study help the researcher to find out how the change is happening and why the change become necessary to the economy, sometimes it might be inflation or otherwise deflation, any situation which will have a long run impact over the economy forces central bank to come up with new monetary Policy.